Asymmetric hybridization origin of Rhododendron agastum (Ericaceae) in Guizhou, China - Li, Qian; Li, Huie; Yang, Lan; Guo, Qiqiang; Fu, Yaru; Huang, Jiayong (Phytotaxa, 2021)
Rhododendron is one of the famous flowers in the world. Four wild Rhododendron species, namely, R. delavayi Franch., R. agastum Balf. f. et W. W. Smith., R. decorum Franch., and R. irroratum Franch., belong to subgenus Hymenanthes, which are sympatrically distributed in the Baili Rhododendron Nature Reserve of Guizhou Province, China. The intermediate morphology of R. agastum in the reserve, which is between R. delavayi and R irroratum or between R. delavayi and R. decorum, has been speculated that R. agastum is a hybrid of one of the two combinations. However, the exact parentage of R. agastum in the reserve remains controversial. In this study, the four Rhododendron species were investigated to identify the parental origin of R. agastum based on 13 morphological characteristics, 20 co-dominant inherited microsatellite markers, and two maternal inherited plastid DNA makers. Results of genetic structure and origin scenario clearly support that R. agastum is a natural hybrid between R. delavayi and R. irroratum rather than R. delavayi and R. decorum, which is consistent with their morphological characteristics. In addition, hybridization analysis indicates that R. agastum is dominated by F2 generation in the reserve. Furthermore, haplotype analysis suggests that natural hybridization between R. delavayi and R. irroratum is bidirectional but asymmetric with R. delavayi, the main maternal parent of R. agastum. Our results provide theoretical basis for future utilization and conservation of genetic resources of these Rhododendron species.